Stroboscopic training effect on anticipating the direction of tennis serves - Boiangin. N. M. (Florida State University, 2019)
he purpose of the study was to examine the effects of stroboscopic training on intermediate tennis players` anticipatory response accuracy, response time, and self-efficacy. Participants (N=30) completed six on-court training sessions, where they returned serves for 30 minutes in their respective condition (i.e., stroboscopic medium frequency, stroboscopic low frequency, placebo glasses without a stroboscopic effect). Additionally, participants watched videos of tennis serves occluded just after racket-ball contact and were asked to anticipate the direction of the serve as quickly as possible. Measures collected included anticipatory response accuracy (i.e., number of correct responses), response time, and self-efficacy and were recorded four times throughout the study (i.e., pre, mid, post and 1-week after training). RM ANOVA analyses indicated that there were no significant differences among the groups for anticipatory response accuracy, response time and self-efficacy. Follow-up one-way ANOVAs indicated significant anticipatory accuracy response differences between the low frequency stroboscopic group as compared to the medium frequency and placebo groups. Specifically, subjects in the low frequency group were more accurate in their anticipatory response compared to the other groups. In general, it seems that stroboscopic training has little (or no) effect on anticipatory response of tennis serves. This study is unique because of the ecologically valid methods used in anticipatory training and measurement. Although the current study supports the notion that stroboscopic training does not improve anticipatory responses in tennis serves, additional research is necessary to examine other stroboscopic training methods (e.g., longer sessions for a longer period, different stroboscopic frequencies) and anticipatory response measurements (e.g., on court response to live serves) in tennis and other sports (e.g., baseball)